2022
DOI: 10.1039/d2gc01556k
|View full text |Cite|
|
Sign up to set email alerts
|

Fully biomass-derived vitrimeric material with water-mediated recyclability and monomer recovery

Abstract: Covalent adaptable networks (CANs) are polymers which demonstrate both high mechanical strength and self-healing / recyclability, which are important for extending material service lifespan and meeting sustainability demands. However, these...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…60−62,64,66,69−73,111−116 Most studies have reported recovery yield ranging from 50 to 90% (mol % or wt %). 62,[69][70][71][72][73]111,112,114,115,117 A minority of studies have reported ≥90% yield. 60,64−66,103,113,118−120 Only a few studies have demonstrated both 90+% small-molecule recovery yield and full property recovery after reprocessing of vitrimers or CANs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60−62,64,66,69−73,111−116 Most studies have reported recovery yield ranging from 50 to 90% (mol % or wt %). 62,[69][70][71][72][73]111,112,114,115,117 A minority of studies have reported ≥90% yield. 60,64−66,103,113,118−120 Only a few studies have demonstrated both 90+% small-molecule recovery yield and full property recovery after reprocessing of vitrimers or CANs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There is an emerging trend to capitalize on the dynamic covalent chemistry of polymers to achieve the recovery of monomers or small molecules under mild conditions. Dynamic covalent chemistries include associative cases, where the dynamic bonds break and reform simultaneously, and dissociative cases, where bonds break sequentially. Cross-linked polymer networks containing dynamic covalent bonds are called covalent adaptable networks (CANs); purely associative CANs are often called vitrimers. , Various dynamic covalent chemistries present in a range of polymer species have been exploited for monomer or small-molecule recovery. For example, Zhao and Semetey used transcarbamoylation, associative dynamic chemistry, to recover ∼80 mol % carbamates from linear PU.…”
Section: Introductionmentioning
confidence: 99%
“…7 Using zinc acetylacetonate as a catalyst for transesterification, the crosslinked epoxy networks became adaptable by the catalyzed transesterification between ester and hydroxyl groups. Based on their unique and attractive properties, vitrimers have received much research attention and significant progress has been made in recent years, 8 including catalystfree systems, 9,10 biomass-based vitrimers, 11,12 vitrimers based on various dynamic covalent bonds, 13,14 integration of vitrimer features into conventional polymers, 15,16 and vitrimer-based organic-inorganic composites. 17,18 Conventional thermosetting resins, such as epoxy resins, are prepared by a step-growth polymerization employing multifunctional small molecular monomers at high reaction conversions.…”
Section: Introductionmentioning
confidence: 99%
“…23 An optimal way is to realize the chemical recycling of polymeric monomers. 24,25 PHU networks can be easily recycled back to monomers to establish chemical recycling because of the relatively high reactivity of the urethane C−O bond. 17,26 A few reports have been carried out on the chemical recycling of PHU.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the emission of toxic decomposition products will pollute the atmosphere, and excess carbon emissions will exacerbate the greenhouse effect . An optimal way is to realize the chemical recycling of polymeric monomers. , PHU networks can be easily recycled back to monomers to establish chemical recycling because of the relatively high reactivity of the urethane C–O bond. , A few reports have been carried out on the chemical recycling of PHU. Ni and co-workers investigated the chemical recycling of lignin-containing PHU .…”
Section: Introductionmentioning
confidence: 99%